Variable Modal Parameter Identification for Non-Linear Mdof Systems. Part II: Experimental Validation and Advanced Case Study - Y.H. Chong; M. Imregun (Shock and Vibration)
The purpose of Part II is to provide an experimental validation of the methodology presented in Part I and to consider a representative engineering case, the study of which requires a relatively large numerical model. A beam system with cubic stiffness type non-linearity was used in the experimental study. The non-linear response was measured at three locations and the underlying linear system was obtained via linear modal analysis of low-excitation response data. The non-linear parameter variations were obtained as a function of the modal amplitude and the response of the system was generated for other force levels. The results were found to agree very well with the corresponding measurements, indicating the success of the non-linear modal analysis methodology, even in the presence of true experimental noise. An advanced numerical case study that included both inherent structural damping and non-linear friction damping, was considered next. The linear finite element model of a high-pressure turbine blade was used in conjunction with three local non-linear friction damper elements. It was shown that the response of the system could be predicted at any force level, provided that that non-linear modal parameters were available at some reference force level. The predicted response levels were compared against those obtained from reference simulations and very good agreement was achieved in all cases.